The Problem of Managing Community Security in The Midst of The Plurality of Security Services - Hoshyar jalal hameed (QALAAI ZANIST SCIENTIFIC JOURNAL, 2022)
This research attempts to track the transformation path that the social security administration has seen problematic in the literature of political systems and its relationship to changing the priorities of decision makers, and consequently, some patterns of the work of the national security services have shifted, by focusing on the transition from management the security file by one apparatus to pluralism in the apparatus Security for the benefit of social security. It also tries to shed light on the repercussions of this with respect to the patterns of public policy making, including the going forward of governments in managing social security and the way in which authoritarian rhetoric refers these issues, from the realm of ordinary issues to issues that give security to them, and thus they are subject to various arrangements when taking thereon. The research concludes that there are caveats against the launch of the security operation in the multiplicity of devices without restrictions, and it is possible that it will lead to a disaster unless it is dealt with and managed in a scientific and sound manner. This is in light of the plurality of the security services, and it is difficult to manage the problems of social security in traditional ways. RatSher, the latest modern methods and means of technology must be followed to manage them in a way that leads to desired and acceptable results.